Sustained censorship in SD (2026-03) (Sudan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Sudan. Data sourced from OONI.
Censorship Incident ID: SD-2026-0030. Severity: critical. Confidence: 72%